2010 Annual International Conference of the IEEE Engineering in Medicine and Biology 2010
DOI: 10.1109/iembs.2010.5626514
|View full text |Cite
|
Sign up to set email alerts
|

Needle steering system using duty-cycled rotation for percutaneous kidney access

Abstract: Abstract-The authors present ongoing work on the use of a variable curvature flexible needle steering system to gain percutaneous access to the kidney for medical interventions. A nonlinear control law is introduced which drives the needle to track a predetermined planar path using a steering approach based on duty-cycled rotation during insertion. Renal access is performed in simulation and tested in vitro in a tissue phantom to validate the proposed control method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 12 publications
0
43
0
Order By: Relevance
“…Adjusting the path intraoperatively in a control-loop has been done in [9] for needle steering in a 2D plane thanks to the use of an extented Kalman filter that estimates the current pose of the needle from image feedback. The path planning consists then in computing a planar arc-trajectory of the needle that links the current tip position to the target thanks to the use of the inverse kinematic model of the needle.…”
Section: Introductionmentioning
confidence: 99%
“…Adjusting the path intraoperatively in a control-loop has been done in [9] for needle steering in a 2D plane thanks to the use of an extented Kalman filter that estimates the current pose of the needle from image feedback. The path planning consists then in computing a planar arc-trajectory of the needle that links the current tip position to the target thanks to the use of the inverse kinematic model of the needle.…”
Section: Introductionmentioning
confidence: 99%
“…Preliminary results revealed that the SMA actuator may be adequate for creating required curvature for geometrically conforming the prostate gland. Wood et al (2010) used a curvilinear approach in clinical practice to introduce steerable needles in transcutaneous medical interventions on the kidney. Orlando et al (2015) compared the adequacy of three methods to control the introduction of SMA needles which were electromagnetic sensors, direct visualization (web camera) and ultrasound.…”
Section: Theoretical Background and Literature Reviewmentioning
confidence: 99%
“…Therefore, it is possible to obtain a desired effective needle curvature K ef f = K(1 − DC) by controlling the duty-cycle ratio DC = Trot T . In [8,10] this method has been implemented by inserting during each cycle the needle on a constant fixed distance ∆z, and by applying a constant rotational velocity ω z = ω c such as:…”
Section: Needle Kinematic Model and Duty-cycling Techniquementioning
confidence: 99%
“…In [7] a kinematic model was proposed for bevel-tip needle steering by constantly spinning the needle during its insertion. This model allows proportional control of the needle curvature and was used in a control-loop that online adapts the evolution of the needle trajectory along an arc in a 2D plane [8]. Other approaches based on the RRT algorithm were proposed to take into account obstacles during the path planning.…”
Section: Introductionmentioning
confidence: 99%